A multidonor–photosensitizer–multiacceptor triad for long-lived directional charge separation. Issue 42 (16th October 2017) - Schlotthauer, Tina; Schroot, Robert; Glover, Starla; Hammarström, Leif; Jäger, Michael; Schubert, Ulrich S.
Abstract : A modular chemistry-on-the complex strategy was applied to assemble a defined block-copolymer-type architecture. After selective excitation of the central photosensitizer unit, charge separation up to several microseconds was observed between the discrete donor and acceptor chains. Abstract : The modular assembly of a directional photoredox-active multidonor–photosensitizer–multiacceptor (Dn –P–Am ) architecture is presented. The triad assembly features a central Ru(ii ) sensitizer equipped with pendant polymer chains consisting of multiple triarylamine (pTARA) and naphthalene diimide (pNDI) units, respectively. Upon excitation, the efficient formation (>96%) of charge separation (CS) was observed featuring similar CS lifetimes (400 ns) as related molecular triads. In contrast, a significant additional longer-lived CS component (2400 ns, 30%) is observed indicating multiple contributing pathways.